2006
DOI: 10.1111/j.1399-3038.2006.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergic rhinitis and nasal smear eosinophilia in 11‐ to 15 yr‐old children in Shiraz

Abstract: Allergic rhinitis (AR) is a common condition among schoolchildren. The prevalence rate of AR differs among countries and even among regions within the same country. The objective of this study was to determine the prevalence of nasal symptoms and signs of AR and nasal smear eosinophilia in 11- to 15-yr-old children in Shiraz. A total of 4584 children aged 11-15 yr of both sexes were surveyed from May 1995 to April 1996, and nasal symptoms and signs of AR (sneezing, rhinorrhea, nasal blockage, itching, color ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
5
18
0
5
Order By: Relevance
“…The prevalences of allergic rhinitis and atopic eczema in 13-to 14-year-old schoolchildren in Urmia city, in Northwest Iran, have been reported to be 23.6 and 10.1%, respectively (Rahimi Rad et al 2007). In Shiraz city, in Central Iran, the rate of allergic rhinitis was estimated at 22% (Miri et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalences of allergic rhinitis and atopic eczema in 13-to 14-year-old schoolchildren in Urmia city, in Northwest Iran, have been reported to be 23.6 and 10.1%, respectively (Rahimi Rad et al 2007). In Shiraz city, in Central Iran, the rate of allergic rhinitis was estimated at 22% (Miri et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a large study in Iran that included 4,584 school-aged children with allergies, the first epidemiologic survey of childhood AR in that country, showed that the frequency of rhinorrhea (92%) exceeds that of nasal obstruction (84%) among those with nasal symptoms and signs of eosinophilia [4]. Prevalence data from five European countries that included 1,482 patients with AR found that rhinorrhea occurs in nearly 70% of patients affected by both SAR and PAR and 57% of AR patients overall [5].…”
Section: Epidemiologymentioning
confidence: 99%
“…While nasal congestion has been identified as one of the most bothersome and prevalent symptoms of AR, it is underappreciated that many patients find rhinorrhea also to be bothersome [4][5][6][7][8]. Rhinorrhea as a symptom of AR virtually never occurs alone; about 97% of patients with AR suffer from at least two symptoms [5], a finding that underscores the advantage of treating a broad range of symptoms with a single medication.…”
Section: Introductionmentioning
confidence: 98%
“…Atrophic rhinitis Comorbidities, associating allergic rhinitis, were examined and quality of life summarily assessed, as, subjective degree of disturbance to sleep and daily life activities. Nasal mucosa scraping was taken, from surface of middle third of inferior turbinate with wooden rhinoprobe and eosinophilic/basophilic infiltration was inspected, to objective ascertaining of allergic rhinitis [23][24] .…”
Section: Methodsmentioning
confidence: 99%